Ali-ibn-Sahl Rabban al-Tabari - Anwar, Zahida; Zahra, Kanwal (International Journal of Pathology, 2018)
Ali-ibn-Sahl Rabban al-Tabari, commonly known as Abu-AL- Hassan, was an eminent scholar of 9th century. Born to a renowned family of Khurasan (near present day Tehran) he marked a name as a physician in the history of medicine. He got his early education in the field of medical sciences, calligraphy, mathematics, philosophy and literature from his father Sahl who himself was a famous physician and a high level state official of his time. Ali ibn Sahl Rabbān received his preliminary education in medical and natural sciences, calligraphy, mathematics, philosophy and literature from his father. In addition to Arabic, Persian and Syriac, he had also mastered the Hebrew and Greek languages to a high degree of proficiency. He translated his own book Firdous al-hikma written in Arabic into the Syriac language.